2018
DOI: 10.19044/esj.2018.v14n3p179
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and Consumption Patterns of Soybean, Moringa Oleifera, Aloe Vera and Other Agro-Resources: The Case of the Elderly and Pregnant/Nursing Women in Lome, Togo

Abstract: Purpose: To assess how soybean products and other agro-resources are known and consumed by some vulnerable populations in Lome (Togo). Methods: A cross sectional study was conducted from March to April 2015 among people aged 50 years and over attending two Pension Fund departments and pregnant and nursing women attending Bè Hospital in Lome. Data were collected using a pre-tested face-to-face questionnaire. Participants were surveyed about their knowledge and consumption habits of soybean, Moringa oleifera, Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…The intake rate of fresh MS leaves among pregnant women was 49.60%. This is higher than previous studies in adults in central Ethiopia and Africa ( 39 , 42 ), but lower than studies in Mauritius, Togo, and India ( 39 , 40 , 44 ). A possible explanation for this difference is probably the difference in culture, food habits, and awareness of the study participants.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The intake rate of fresh MS leaves among pregnant women was 49.60%. This is higher than previous studies in adults in central Ethiopia and Africa ( 39 , 42 ), but lower than studies in Mauritius, Togo, and India ( 39 , 40 , 44 ). A possible explanation for this difference is probably the difference in culture, food habits, and awareness of the study participants.…”
Section: Discussioncontrasting
confidence: 70%
“…Studies on consumption of MS species showed that it was widespread practice: 63% in India ( 39 ), 81% in Africa ( 39 ), 87.2% in Togo ( 40 ),and 90% in South Africa ( 41 ) but it has been underutilized (36%) in East Shoa Zones of Oromia,Ethiopia ( 42 ). Age, education level, marital status, occupation, household wealth status, awareness level, knowledge of plant biology, gender, and family size ( 43 , 44 ) were factors associated with MS species consumption in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Fetal growth and development also depend on other essential nutrients, like vitamins. Many studies have shown that the deficiency of micronutrients such as magnesium, zinc and iron is associated with abnormal fetal development and risk of miscarriage ( Mensah et al 2018 ). However, the importance of vitamin deficiency has been somewhat overlooked as well as the importance of the antioxidant status of the mother and the fetus.…”
Section:  Morphological and Physiological Characteristics Of The Pelmentioning
confidence: 99%